A Contribution to a Western Genealogy of the Rights of Men, and Incidentally, of Women - Baldissone, Riccardo (LexisNexis Betterworths, 2011)
This paper explores the transformation of the concept of rights through the contingencies of Western cultural history. It follows the emergence of an autonomous nomos in fifth-century BCE Greece, and it surveys Roman law and its recovery in the eleventh-century during the Papal Revolution, which first applied in the Western world to the whole society the Platonic program of founding the polity upon principles. Such foundationalist approach was restated in modern times by Hobbes' absolutely individualist anthropology, whose overcoming requires both the questioning of Western theological and naturalistic aperspectival stances, and the opening of radically participatory paths.